The Implementation of Biofloc Systems in the Catfish Breeding Cooperated with Lele Tamora SME - Zuhra, Cut Fatimah; Sovia, Sovia Lenny; Nunuk, Nunuk Priyani (Talenta Publisher, 2019)
This community service aims to provide solutions for fisheries that experience water change problems caused by the lower availability of ground water. The small-medium enterprise (SME) Lele Tamora which is engaged in catfish breeding experiences this problem, such as turbid and bubbly water, which causes mass death of fish seedlings. Therefore, pond fish farming with a modern system integrated by a biofloc system that is supported by the use of microbubbles is introduced to the owner. The basic principle of this system is to utilize bacteria that can release substances that function as adhesives to form biofloc, such as microalgae aggregates, residual pellets, exoskeletons of dead organisms, bacteria, protists, protozoa and others substance with 0.1-2 mm diameter. All of these aggregates can be a source of poison in the pond system or as a competitor for fish to get oxygen. The biofloc system is projected to be able in reducing the toxic content in pond water which automatically reduces fish mortality, and this system can also convert organic waste in ponds into natural food as well as reducing commercial feed. For this purpose, a 1000 liter volume of bioreactor has been constructed to grow biofloc bacterial seeds, 20-liter-capacity of autoclaves to sterilize dissolved oxygen while helping to breed floc-forming aerobic bacteria. This system has been implemented at Lele Tamora SME, and the results showed the changing of water-pond colour from green to brown. Meanwhile, the netting ratio (selection of catfish based on the size of ready-to-sell) increased from 4000 to 8000 individuals.